A preview on the conceptualization of contemporary knowledge from Islamic knowledge management perspective / Muhamadul Bakir Hj. Yaakub, Khatijah Othman and Ahmad F. Yousif - Othman, Khatijah; Yousif, Ahmad F. (Faculty of Business and Management, 2015)
The philosophy of knowledge is known as an established discipline both from Islamic perspective and Western viewpoint. Generally, it can be understood as a source of economy, power and prosperity. With the knowledge as a source of provider, the economic development, political power, business transaction and networking; rapid development in telecommunication and technology, with various other developments in human engineering and education plus, etc.‟s; human civilization flourishes. Focusing on the philosophy of knowledge and comparing its traditional sense with modern practice might lead us to discover some ways in which knowledge should be realized, managed and applied. Obviously, the issue and criteria that determine what constitutes knowledge is indeed crucial. Therefore, this paper highlights general concept of knowledge management from Islamic perspective and its significant contribution to human development.